Cyprinid herpesvirus 2 infection changes microbiota and metabolites in the gibel carp (Carassius auratus gibelio) midgut - Chen, Peng; Zhang, Mingming; Zhang, Yichan; Li, Jun; Wan, Xihe; Lv, Tingli; Chen, Yiyue; Zhao, Zhigang; Ma, Zhihao; Zhu, Zhu; Chen, Lihua; Li, Zhen; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Cyprinid herpesvirus 2 (CyHV-2) infects gibel carp (Carassius auratus gibelio) and causes severe losses. Microbiota in animal guts involves nutrition intake, development, immunity, and disease resistance. However, the relationship between gibel carp gut microbiota and CyHV-2 infection is not well-known. Herein, we analyzed the gut microbiota composition and metabolite profiles in CyHV-2-infected and uninfected fish using high-throughput sequencing and gas chromatography/mass spectrometry. Results showed that CyHV-2 infection significantly changed gut microbiota and metabolite profiles (p < 0.05). High-throughput sequencing demonstrated that the relative abundance of Aeromonas increased dramatically while Cetobacterium decreased. Time-course analysis showed that the number of Aeromonas in the midgut of infected fish increased more than 1,000 times within five days post-infection. Metabolome analysis illustrated that CyHV-2 infection significantly altered 24 metabolites in gibel carp guts, annotating to the anomaly of digestion and metabolisms of amino acids, carbohydrates, and lipids, such as tryptophan (Trp) metabolism. Mantel test demonstrated that gut microbiota and metabolite profiles were well-related (r = 0.89). Furthermore, Trp metabolism response to CyHV-2 infection closely was taken as one example to prove the correlation between CyHV-2 infection, metabolites in the gut, and host immunity. Results showed that modulating Trp metabolism could affect CyHV-2 replication and transcription of anti-viral cytokines. Therefore, we conclude that CyHV-2 infection significantly perturbed the gut microbiome, disrupted its’ metabolic functions, and caused the proliferation of the opportunistic pathogen Aeromonas. Also, this study suggests that modulation of the gut microbiome will open a therapeutic opportunity to control CyHV-2 infection.